Allometric Biomass Equations For Tree Species Used In Agroforestry Systems In Uganda - Tumwebaze, Susan Balaba; Bevilacqua, Eddie; Briggs, Russell; Volk, Timothy (Agroforestry systems, 2013)
Estimates of above-ground biomass are required for better planning, sustainable management and monitoring of changes in carbon stocks in agroforestry systems. The objective of this study was to develop and compare biomass equations for Markhamia lutea, Casuarina equisetifolia, Maesopsis eminii and Grevillea robusta grown in a linear simultaneous agroforestry system in Uganda. These species were established in single rows in the middle of fields in 1995 from four-month old seedlings. A total of 57 trees were sampled for this study, 13 for M. lutea, 12 for C. equisetifolia, 16 for M. eminii and 16 for G. robusta. Biomass values of the various tree components (stem, branches and foliage) as well as the total above-ground biomass were fitted to linear and non-linear allometric models using total height, diameter-at-breast height (DBH), crown width as predictor variables. Although both DBH and height are typically used as independent variables for predicting above-ground biomass, the addition of height in biomass equations did not significantly improve model performance for M. eminii, M. lutea and G. robusta. However, addition of height significantly increased the proportion of variation explained in above-ground biomass for C. equisetifolia, while DBH did not significantly improve the prediction of biomass. The study confirmed the need for developing species-specific biomass equations.
Keywords: Agroforestry Allometric biomass equations Maesopsis eminii Markhamia lutea Grevillea robusta Casuarina equisetifolia